Autonomia e identidade profissional de professores de educação física diante da Proposta Curricular do Estado de São Paulo - Freitas, Tatiana Pereira de (2011)
This research aims to analyze the processes that Physical Education teachers use in order to integrate their knowledges and act autonomously considering the Curricular Proposal of the state of São Paulo for the Physical Education subject. We aim to focus on the autonomy of the subject teachers from the perspectives of the study of the epistemology of the teaching practice and professional identity. The choice of the teacher s autonomy theme has emerged from the observation of the impact of the Curricular Proposal of the state of São Paulo, in 2008, on the school routine and the difficulties faced by the teachers concerning the learning situations elucidated in the proposal, as well as the strategies to be used. The research is oriented by the hypothesis that the teachers autonomy is connected to a continuous reconstruction of their professional identity and the processes they use in order to integrate their knowledges to the requirements of the curricular proposal. We adopt as theoretical reference the studies of Dubar, Contreras and Tardif in order to conceptualize and contextualize autonomy, identity and the teachers professional knowledges, as a fundamental part of the teachers formation, development and performance process. To collect the data a previous study was accomplished in order to define the research subjects: 06 physical education teachers and 03 pedagogic coordinators from 03 different state public primary schools in Itapevi-SP who answered semi-structured interviews, previously tested. Besides the interviews, the research included documental analysis of the curricular proposal. The data obtained were presented in synthesis tables and analyzed concerning the concepts of teachers formation, autonomy, identity and professional knowledges. The results allow us to affirm that: the proposal restricts the Physical Education teachers autonomy concerning the elaboration and planning of their lessons, however, at the same time, it has promoted movements towards new knowledges about the taught subject. The situation of the imposition and requirements of the proposal in which the teachers affirm they are exposed to has resulted in processes of adaptation of the proposal and changes in the pedagogic practice. The autonomy the teachers reveal concerning the proposal depends, on the one hand, on their personal path and professional formation and, on the other hand, on the objective conditions of the pedagogic practice, which are linked to their professional identity. The teachers joined the proposal as a consequence of the valorization of the Physical Education by the different subjects of the school community, after its implementation. The teachers pedagogic practices were, in an extent, changed by the proposal, because they re considered necessary to the proposition of new principles to their work, but kept marked by traditional conceptions of the Physical Education and the preference for the field of sports training, which still remains with the requirements of the new proposal, influencing their teaching practice